Analisis Faktor-Faktor yang Mempengaruhi Pengungkapan Risiko Perusahaan (Studi Empiris Laporan Tahunan Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indoesia (BEI) Pada Tahun 2014) - Yuniarti, Ika; , Dr.Erma Setyawati, Ak.,MM (2016)
This research purpose to see the influence of factors which inluential risk disclosure in the risk management report that is: type of industry, firm size, leverage degree, profitability degree, public ownership structure and institution ownership structure. The population used in this research is annual report firms which is listed in Indonesia Stock Exchange at 2014. Sample in this research is non-finances firms which is listed in Indonesia Stock Exchange at 2014. This research use purposive sampling in carry out sample selection. There are 187 non-finances firms which is listed in Indonesia Stock Exchange at 2014 is become sample in this research. Stakeholder theory and agency theory is used to explain connection inter variable. Act of risk disclosure in this research use content analysis based on the identification of setences act of risk disclosure in the annual report. Test statistic used is multiple linear regression test. The result of this research find type of industry and firm size does not has influence with risk disclosure on firm, where as leverage degree, profitability degree, public ownership structure and institution ownership structure are related significant influence with risk disclosure on firm. However that totaly factors has influence toward act of risk disclosure. Keywords : Risk, risk disclosure, risk management, kind of risk, characteristic of disclosure, stakeholder theory and agency theory.